(untitled) (Journal of actual problems of jurisprudence, 2019)
The article is devoted to management issues in the division system and the ratio of authorities in the Kyrgyz Republic. The historical and legal analysis carried out in the article emphasizes that the installation of political forces between the branches of government and the corresponding attempts to establish the constitutional status and powers of higher and local governments are the main task, the solution of which opens up possibilities for further reform of state structures. In this direction, the author has identified a number of serious contradictions that the republic should overcome. One of them is a proposal for solving institutional and sectoral problems of power.